The Dynamics of SME Digital Marketing in the Digital Business Ecosystem - Fadillah Fadillah; Fismayatni Cholifah; Azzahra Putri; Yulia Fitriani; Mohammad Rizan; Setyo Ferry Wibowo (Greenation Research & Yayasan Global Resarch National, 2025)
The rapid advancement of digital technology has transformed business practices globally, impacting not only large corporations but also Micro, Small, and Medium Enterprises (MSMEs). In the digital era, MSMEs are required to adopt innovative strategies, particularly in marketing, to remain competitive and sustainable. Digital marketing has emerged as a crucial tool for MSMEs to expand market reach, improve operational efficiency, and better engage with consumers through platforms such as social media, e-commerce, and digital analytics. In Indonesia, digital adoption among MSMEs is growing significantly. As of December 2023, approximately 41.2% of MSMEs have integrated into the digital ecosystem, with the government targeting 30 million MSMEs to be digitalized by 2024. Despite the promising growth and numerous benefits such as increased revenue and market access MSMEs still face major challenges including limited digital literacy, inadequate infrastructure, and financial constraints. This study aims to conduct a literature review on the dynamics of digital marketing among MSMEs within the digital business ecosystem. It seeks to explore the factors influencing the effectiveness of digital marketing strategies, the challenges faced in their implementation, and the adaptive measures adopted by MSMEs. The findings are expected to provide strategic insights for MSME development and inform policymakers in creating a supportive digital economic environment. Ultimately, this review aspires to contribute to the formulation of inclusive and sustainable digital marketing strategies for MSMEs in Indonesia.